1982
DOI: 10.1029/jb087ib08p06489
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stratigraphy, Iceland Research Drilling Project, Reydarfjordur, eastern Iceland

Abstract: Major element data are reported for lavas and dikes from a 3.2‐km section through the eastern Iceland lava pile. The section includes a 1.2‐km subaerial exposure and a 1.9‐km sequence drilled by the Iceland Research Drilling Project (IRDP). Alteration increases down‐section, although primary magma chemistry may be interpreted from FeO* Al2O3, TiO2, P2O5 and (to a lesser extent) SiO2 in addition to immobile trace elements. Lava compositions range from MgO‐rich tholeiite to SiO2‐rich icelandite, while dikes rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The second composition is identical to the first in all respects save Fe (in which the second composition is poorer), Al (richer), and Ca (slightly richer). The relative abundances of Fe and Al in the second composition (Fe/Al = 0.4) typify those of terrestrial basalt [e.g., Leeman et al , 1990; Flower et al , 1982] and satisfy compositional constraints posed by deconvolved thermal emission spectrometer (TES) data from the Mars surface [e.g., Hamilton et al , 2001]. Some experimentalists have also proposed that moderate‐Fe/Al basalts are parental to Mars meteorite materials [ Nekvasil et al , 2007].…”
Section: Methodsmentioning
confidence: 99%
“…The second composition is identical to the first in all respects save Fe (in which the second composition is poorer), Al (richer), and Ca (slightly richer). The relative abundances of Fe and Al in the second composition (Fe/Al = 0.4) typify those of terrestrial basalt [e.g., Leeman et al , 1990; Flower et al , 1982] and satisfy compositional constraints posed by deconvolved thermal emission spectrometer (TES) data from the Mars surface [e.g., Hamilton et al , 2001]. Some experimentalists have also proposed that moderate‐Fe/Al basalts are parental to Mars meteorite materials [ Nekvasil et al , 2007].…”
Section: Methodsmentioning
confidence: 99%
“…A compilation of the chemical data collected from the deep drill hole at Reydarfjordur (FLOWER et al, 1982) is shown by Figure 12. The only Mgrich lavas shown here are the few picrites of the Reykjanes Peninsula, which are the most notable such rocks in Iceland (e.g., JAKOBSSON et al, 1978).…”
Section: Iceland's Rhyolites and Granophyresmentioning
confidence: 99%
“…The di¡erence in P-wave seismic velocity between the olivine basalts and the basaltic andesites/Icelandites is approximately 0.5 km s {1 . The plagioclase cumulates identi¢ed by Flower et al (1982) have a fairly ma¢c composition and a similar estimated velocity to the low-Mg basalts (Fig. 9).…”
Section: Stratigraphic Lava Groups: Compositional Variationmentioning
confidence: 71%
“…Furthermore, the di¡erences in lava composition between the groups a¡ects the average seismic velocity of each group. To estimate the e¡ect of compositional variation between lava groups we have taken the major element composition of 292 lavas within the ReydarfjÎrdur lava pile (from Flower et al 1982), estimated the norm mineralogy for ¢ve petrological groups (after Robinson et al 1982) using the CIPW scheme (Cross et al 1903) and proceeded to estimate seismic velocities for these rocks using the Voigt^Reuss^Hill averaging scheme (Hill 1952) with mineral properties from Carmichael (1990) and Qiu, Priestley & McKenzie (1996) (Fig. 9).…”
Section: Stratigraphic Lava Groups: Compositional Variationmentioning
confidence: 99%